(untitled) (Veterinary Science, 2017)
The balanced food for laying hens may be contaminated with strains of fungi. The mycotoxins produced by them generate economic and productive problems in birds, such as decreased production; lose of overall state and death in extreme cases. The mycotoxins that affect more birds are aflatoxins produced by Aspergillus species. The aim of this study was to relieve the presence of aflatoxins in commercial food and manufactured by producers for laying hens in the city of General Pico, La Pampa. The samples obtained were analyzed by the ELISA method. The presence of toxic levels of aflatoxins was determined in 77.8% of the analyzed samples. The manifestation of Aflatoxins in food is a result of the lack of quality controls of the raw materials and inadequate storage systems. These results determine the need for preventive measures for food handlers to avoid risks to which they are exposed. Meanwhile, the use of sequestrants is the most appropriate indication to reduce toxic effects on birds and avoid production losses